Effect of Clitoria Ternatea as Adjuvant Therapy on Serum Cortisol Levels in Leprosy Reaction - Rina Purnamasari; Muflihatul Muniroh; Novi Kusumaningrum; Farmaditya EP Mundhofir; Renni Yuniati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
This study was to investigate the effect of using an extract from Clitoria ternatea as adjuvant therapy on the levels of blood cortisol in patient with leprosy reaction. The current investigation is an experimental study designed a single-blind randomized controlled trial comparison between two groups. The control group which received standard prednisolone therapy and the intervention group received standard prednisolone therapy and adjuvant therapy of Clitoria ternatea extract dose 2 g/day for one month. Serum levels of cortisol were measured by ELISA. The average serum level of cortisol decrease in control grup with statistically significant (p=0.008). The average serum level of cortisol increase in treatment grup with statistically significant (p=0.026) similar with average difference of both groups (p=0.02). According to the results of the study, the use of an extract from Clitoria ternatea extract 2 g / day for one month as adjuvant therapy significantly increase the serum cortisol levels in patients with leprosy reaction